Analysis of Government Expenditure on Inclusive Economic Development in Papua - Pisi Bethania TITALESSY; Radian Januari SITUMEANG (International Journal of Environmental, Sustainability, and Social Science, 2024)
One of the efforts to develop an inclusive economy in the poorest province in Indonesia, Papua, is through fiscal policy. This research has two main objectives, namely: (i) assessing the Inclusive Economic Development in Papua; and, (ii) analyzing the relationship between fiscal policy in realizing Papua Inclusive Economic. Papua Province has the lowest Inclusive Economic Development Index (IEDI) ranking in Indonesia. This low level of caused 26.8 percent of the poor population in Papua Province. Economic development interventions through fiscal policy need to be carried out. Analysis of regional fiscal policy factors that are significant to the IEDI of each city/district can pay attention to policy directions from the past that need to be prioritized so that policy strategies can be developed. Novelty: This research is the first to observe Papua's IEDI through government expenditure factors. This research is the first that show how statistically to modelling IEDI. The fiscal policy is observed through the budgeting of the General Allocation Fund (GAF), Physical Special Allocation Fund (PSAF), Non-Physical Special Allocation Fund (NPSAF), and Village Fund (VilF). Data is observed in 2019 to 2021. Panel data regression model is used to analysis the effect of expenditure. The REM model obtained gives an R-sq of 41.9% with high IEDI prediction accuracy. This study found that PSAF and NPSAF were the source of the increase in IEDI. These findings indicate that the PSAF and NPSAF (physical and non-physical) is more efficient than the GAF and VilF on inclusive economic development in Papua.